CIC-rearranged round cell (Ewing-like) sarcoma of the uterus: Review of the literature - Shaina Sedighim; Jonathan Burke; Douglas Schneider; Talia Kamdjou; Julio A. Diaz-Perez; Jonathan Trent; Mecker Möller (Elsevier, 2020)
CIC-rearranged round cell sarcoma (CRS) is a rare entity that presents in various anatomical locations and involves deep soft-tissue structures and skin. Although commonly confused with and clinically similar to Ewing sarcoma (ES), investigators have recently shown that this unique condition maintains morphologic and pathologic features that are distinct from ES. In this report, we present and discuss a case of CRS of the uterus, the first of its kind to be reported in the English-language literature. We urge the scientific community to continue its investigations in elucidating the features of this entity, as young women who suffer from this condition have dismal prognoses and currently do not have access to therapeutic options for cure.